2013
DOI: 10.13066/kspm.2013.8.1.117
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Trunk Muscle Strengthening Exercises on Balance Performance of Sitting Posture and Upper Extremity Function of Children with Spastic Diplegic Cerebral Palsy

Abstract: PURPOSE: The purpose of this study was to investigate the effect of trunk muscle strengthening exercises on balance performance of sitting posture and upper extremity function, targeting the children with spastic diplegic cerebral palsy. METHODS: 20 children with spastic diplegic cerebral palsy were sampled at random and the tests were conducted for 6 weeks, 3 times per week. For experimental groups, basic physical therapy and trunk muscle strengthening exercises were conducted and for control groups, only bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…These results are similar to those of a previous study in which neck flexion exercises and bridge exercises improved sitting position trunk control for children with cerebral palsy 15 ) . Trunk stabilization exercises are a basic component of the motility of the distal part of the body, including neck movements; several studies have shown the importance of trunk stabilization exercises for these movements 16 , 17 ) . Furthermore, children with spastic cerebral palsy are characterized by trunk muscle weakness, which has direct effects on the functional performance of activities of daily living, and insufficient static and dynamic balance abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to those of a previous study in which neck flexion exercises and bridge exercises improved sitting position trunk control for children with cerebral palsy 15 ) . Trunk stabilization exercises are a basic component of the motility of the distal part of the body, including neck movements; several studies have shown the importance of trunk stabilization exercises for these movements 16 , 17 ) . Furthermore, children with spastic cerebral palsy are characterized by trunk muscle weakness, which has direct effects on the functional performance of activities of daily living, and insufficient static and dynamic balance abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed improving balance ability among children with cerebral palsy. Choi et al reported that trunk muscle strengthening exercises positively affected upper limb functions and balance ability among children with cerebral palsy 9 ) . Similarly, McBurney et al reported that when lower limb muscle strengthening exercises were applied to 11 spastic paraplegic children with cerebral palsy, lower limb muscle strength, flexibility, postures, and gait ability were improved; this study’s findings also emphasized the importance of strengthening exercises for improving trunk stability 10 ) .…”
Section: Introductionmentioning
confidence: 99%
“…However, according to previous studies, children with CP have sensory processing issues as well as motor problems, which lead to severe developmental disability (Ahn et al, 2004;Choi et al, 2013). CP sufferers with sensory modulation problems, poor sensory registration and sensory discrimination deficits show delay issues regarding level of arousal, attention, motivation, behavioral organization, and action planning, which also affects motor functions (Ayres and Tickle, 1980;Beckung and Hagberg, 2002).…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…This causes difficulties in the voluntary movements of all limbs and, in particular, weakening of the abdominal muscles induces not only functional difficulties in normal development but also problems in respiratory functions 38 ) . It is asserted that execution of trunk muscle strengthening exercise by children with cerebral palsy can help with the improvement of respiratory functions by not only improving the trunk stability, and functions and balancing ability of upper arms but also imparting influence on pulmonary functions 39 , 40 ) . In addition, Vera-Garcia et al 41 ) also reported that the level of activation of abdominal muscles including rectus abdominis and oblique muscles of abdomen, etc.…”
Section: Discussionmentioning
confidence: 99%